Sleep Effort and Insomnia Severity: The Role of Bedtime Procrastination - Omer Faruk Uygur; Aynur Bahar (Sleep Medicine Research, 2023)
Background and Objective We aimed to investigate the mediating role of bedtime procrastination in the relationship between sleep effort and insomnia severity in this study. Methods We included 497 university students in this study. All the participants completed the sociodemographic data form, Glasgow Sleep Effort Scale (GSES), Insomnia Severity Index (ISI), Depression-Anxiety-Stress Scale-21 (DASS-21), and Bedtime Procrastination Scale (BPS). We divided the participants into groups, according to their GSES and BPS scores, those with high-low sleep effort and those with BP (+) and BP (-), respectively. We compared the variables in these groups. Finally, we analyzed the mediating role of bedtime procrastination in the relationship between sleep effort and insomnia severity. Results The mean age of the participants was 20.41 ± 1.83 years. ISI, BPS, and DASS-21 were statistically significant in the group with high sleep effort (p < 0.01). Among the psychometric instrument scores, the highest correlation with GSES was with ISI, and then there was a statistically significant positive correlation with DASS-21. In addition, there was a statistically significant positive correlation between GSES and BPS. Bedtime procrastination played a partial mediation role in the relationship between sleep effort and insomnia severity. Conclusions Bedtime procrastination partially mediated the relationship between sleep effort and insomnia severity. Therapists should consider sleep effort and bedtime procrastination on their agenda in cognitive behavioral therapy sessions for insomnia.